PECULIARITIES OF IDIOMATIC EXPRESSIONS IN ENGLISH AND UZBEK LANGUAGES BASED ON MASS MEDIA (Journal of Universal Science Research, 2025)
This thesis explores the peculiarities of idiomatic expressions in English and Uzbek languages with a focus on their usage in mass media. It  analyzes the theoretical background of idioms, their applications in mass media, and provides a comparative analysis of idiomatic expressions in English and Uzbek newspapers.